Mesenchymal Stem Cells from Wharton's Jelly and Amniotic Fluid. (February 2016) - Joerger-Messerli, Marianne S.; Marx, Caterina; Oppliger, Byron; Mueller, Martin; Surbek, Daniel V.; Schoeberlein, Andreina
Abstract : The discovery of mesenchymal stem cells (MSCs) in perinatal sources, such as the amniotic fluid (AF) and the umbilical connective tissue, the so-called Wharton's jelly (WJ), has transformed them into promising stem cell grafts for the application in regenerative medicine. The advantages of AF-MSCs and WJ-MSCs over adult MSCs, such as bone marrow-derived mesenchymal stem cells (BM-MSCs), include their minimally invasive isolation procedure, their more primitive cell character without being tumourigenic, their low immunogenicity and their potential autologous application in congenital disorders and when cryopreserved in adulthood. This chapter gives an overview of the biology of AF-MSCs and WJ-MSCs, and their regenerative potential based on the results of recent preclinical and clinical studies. In the end, open questions concerning the use of WJ-MSCs and AF-MSCs in regenerative medicine will be emphasized. Highlights: Wharton's jelly (WJ) and amniotic fluid (AF) are more primitive that adult mesenchymal stem cells (MSC), but not tumorigenic. Preclinical and clinical studies suggest the safe and efficacious use of WJ-MSCs and AF-MSCs in future stem cell therapies. WJ-MSCs and AF-MSCs are regenerative due to their migration, differentiation, secretome and immunomodulatory properties.